Risk Factors for Readmission in Patients With Ovarian, Fallopian Tube, and Primary Peritoneal Carcinoma Who Are Receiving Front-line Chemotherapy on a Clinical Trial (GOG 218): An NRG Oncology/Gynecologic Oncology Group Study (ADS-1236). Issue 1 (January 2016) - Duska, Linda R.; Java, James J.; Cohn, David E.; Burger, Robert A.
Abstract : Obstet Gynecol Surv 2016;71(1):24–26 Patients with ovarian cancer are at high risk of readmission after primary cytoreductive surgery and chemotherapy. Specific risk factors for rehospitalization are not defined. To develop strategies to decrease readmissions, risk factors predictive for readmission must be identified.